Curable composition and cured product thereof
By combining the cured body of the electrical insulating material under specific conditions with the olefin-aromatic vinyl compound-aromatic polyene copolymer under specific conditions, the deficiencies of the thermoplastic composition or cured body in the prior art in terms of low dielectric properties and mechanical strength are solved, and excellent low dielectric properties and high mechanical properties are achieved.
Patent Information
- Application Number
- CN202080083049.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-05-20
- Filing Date
- 2020-12-01
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2040-12-01
AI Technical Summary
It is difficult to obtain thermoplastic compositions or cured bodies with excellent low dielectric properties and high mechanical strength, especially at high temperatures.
A cured body of an electrical insulating material is formed by using an olefin-aromatic vinyl compound-aromatic polyene copolymer that meets specific conditions and is combined with a selected additive resin. The number average molecular weight of the copolymer of the composition is between 50 million and 100,000, the monomer content of aromatic vinyl compound is between 0% and 70%, the vinyl content of aromatic polyene is between 1.5 and 20, and the olefin monomer content is appropriate.
The excellent low dielectric properties and high mechanical strength of the cured body are achieved, especially the elastic modulus and fracture strength at room temperature and high temperatures are significantly improved, and at the same time they have good adhesion and dimensional stability.
Smart Images

Figure BDA0003665576740000141 
Figure BDA0003665576740000142 
Figure BDA0003665576740000151
Abstract
Description
Technical Field
[0001] The present invention relates to a composition. In this specification, the term "sheet" also includes the concept of a film. In addition, in this specification, even if a term "film" is described, the term "sheet" also includes the concept of a film. Background Art
[0002] Because communication frequency develops to gigahertz band and higher high frequency band, therefore, the demand for insulating materials with low dielectric properties also becomes high thereupon.With regard to aromatic vinyl compound polymers such as polyolefins such as polyethylene, polystyrene, owing to not having polar groups in molecular structure, therefore as the material showing excellent low dielectric constant, low dielectric loss tangent and known.But the heat resistance of these polymers depends on crystal melting point or glass transition temperature, therefore there is problem aspect the heat resistance as electrical insulator, in addition, owing to being thermoplastic resin, therefore there is problem aspect film making process (patent documentation 1).
[0003] Fluorine resins such as perfluoroethylene have excellent low dielectric constant, low dielectric loss and excellent heat resistance, but are difficult to form and process, film forming, and the device suitability is low. In addition, there are also problems in the bonding strength between wiring and copper foil. On the other hand, substrates and insulating materials using post-curing resins such as epoxy resins, unsaturated polyester resins, polyimide resins, and phenolic resins are widely used because of their heat resistance and ease of operation, but dielectric constants and dielectric loss are higher, and as insulating materials for high frequency use, it is expected to be improved (patent document 2).
[0004] An electrical insulating material (patent document 3) formed by grafting or block copolymers comprising olefin polymer segments and styrene polymer segments has been proposed. This material focuses on the low dielectric constant and low dielectric loss properties of hydrocarbon polymers of olefins and styrene. Its manufacturing method is to make commercially available polyethylene and polypropylene carry out conventional graft polymerization in the presence of styrene monomer, divinylbenzene monomer and free radical polymerization initiator. Such a method has the problem that grafting efficiency cannot be improved and the uniformity of polymer is not enough. In addition, the polymer obtained contains gel, and there is a problem of poor processability and filling. This material is a thermoplastic resin, and heat resistance is insufficient, and it is necessary to add heat-resistant resins such as 4-methyl-1-pentene system. This material is difficult to be applied in a molding method that is cured after being coated or filled in a specified position.
[0005] Patent Document 4 describes an insulating layer formed of a crosslinked structure containing a hydrocarbon compound having a plurality of aromatic vinyl groups as a crosslinking component. The cured product of the crosslinking component described specifically in the examples is rigid and is considered difficult to fill with a large amount of filler.
[0006] Patent documentation 5 discloses a solidified body obtained by a specific polymerization catalyst, and the solidified body is formed by a specific composition, ethylene-olefin (aromatic vinyl compound)-polyene copolymer, and a non-polar vinyl compound copolymer. The solidified body specifically recorded in the embodiment of patent documentation 5 has the characteristics of low dielectric constant and low dielectric loss tangent, but because it is soft, it is necessary to improve the mechanical strength such as elastic modulus at normal temperature and high temperature. In the interlayer insulating material and cover layer purposes of the insulating material of the film such as FPC, FCCL, it is preferred to improve the dimensional stability such as the thickness during the installation process or during the use period after installation. In addition, the solidified body of the composition specifically recorded in the embodiment has room for improvement in the adhesion with metal foil (especially copper foil). Patent documentation 6 discloses a solidified body obtained by the same specific polymerization catalyst, and the solidified body is formed by a specific composition, ethylene-olefin (aromatic vinyl compound)-polyene copolymer, and a non-polar vinyl compound copolymer, but the solidified body of the composition specifically recorded in the embodiment also has room for improvement in the adhesion with metal foil (especially copper foil) and low temperature characteristics. Patent Document 7 also describes a cured product of a composition containing the same copolymer, but the cured product of the composition specifically described in the examples has room for improvement in terms of adhesion to metal foil (particularly copper foil).
[0007] Patent documents 5, 6, and 7 disclose a solidified body obtained by a specific polymerization catalyst, which is formed by a specific composition, a coordinated ethylene-olefin (aromatic vinyl compound)-polyene copolymer and a non-polar vinyl compound. These curable compositions contain a relatively large amount of monomer components (aromatic vinyl compound, aromatic polyene) and are varnish-like. Therefore, not only are there odors, but there is also a problem that a B-stage sheet (semi-cured body sheet) cannot be easily manufactured. These curable compositions have a problem of making manufacturing equipment complicated.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Publication No. 52-31272
[0011] Patent Document 2: Japanese Patent Application Laid-Open No. 6-192392
[0012] Patent Document 3: Japanese Patent Application Laid-Open No. 11-60645
[0013] Patent Document 4: Japanese Patent Application Publication No. 2004-087639
[0014] Patent Document 5: Japanese Patent Application Publication No. 2010-280771
[0015] Patent Document 6: Japanese Patent Application Publication No. 2009-161743
[0016] Patent Document 7: Japanese Patent Application Publication No. 2010-280860 Summary of the invention
[0017] Problems to be solved by the invention
[0018] In the above-mentioned prior arts, no thermoplastic composition that is easily moldable or a cured product that has excellent low dielectric properties and high mechanical strength (elastic modulus, etc.) at room temperature and at elevated temperatures has been obtained, and it is desired to provide such a composition and cured product.
[0019] Methods for solving problems
[0020] That is, the present invention can provide the following aspects.
[0021] A curable composition comprising an olefin-aromatic vinyl compound-aromatic polyene copolymer satisfying the following conditions (1) to (4), and an added resin, wherein the added resin is one or more selected from the group consisting of hydrocarbon elastomers, polyphenylene ethers, olefin-aromatic vinyl compound-aromatic polyene copolymer oligomers, and aromatic polyene resins.
[0022] (1) The number average molecular weight of the copolymer is 5,000 to 100,000.
[0023] (2) The aromatic vinyl compound monomer is an aromatic vinyl compound having 8 to 20 carbon atoms, and the content of the aromatic vinyl compound monomer unit is 0% by mass to 70% by mass.
[0024] (3) The aromatic polyene is one or more selected from polyenes having a carbon number of 5 to 20 and having a plurality of vinyl and / or vinylidene groups in the molecule, and the content of vinyl and / or vinylidene groups derived from the aromatic polyene unit is 1.5 to less than 20 in terms of number average molecular weight.
[0025] (4) The olefin is one or more selected from olefins having 2 to 20 carbon atoms, and the total of the olefin monomer units, the aromatic vinyl compound monomer units and the aromatic polyene monomer units is 100% by mass.
[0026] An electrical insulating material, which is a cured product obtained from the following composition, wherein the composition comprises an olefin-aromatic vinyl compound-aromatic polyene copolymer satisfying the following conditions (1) to (4), and one or more additional resins selected from the group consisting of hydrocarbon elastomers, polyphenylene ethers, olefin-aromatic vinyl compound-aromatic polyene copolymer oligomers, and aromatic polyene resins, wherein the storage elastic modulus of the electrical insulating material at 300° C. is 5×105 Pa or more, preferably 1×10 6 Pa or more, and the dielectric constant at 23° C. and 10 GHz is 2.5 or less and 2.0 or more, and the dielectric loss tangent is 0.003 or less and 0.0005 or more.
[0027] (1) The number average molecular weight of the copolymer is 5,000 to 100,000.
[0028] (2) The aromatic vinyl compound monomer is an aromatic vinyl compound having 8 to 20 carbon atoms, and the content of the aromatic vinyl compound monomer unit is 0% by mass to 70% by mass.
[0029] (3) The aromatic polyene is one or more selected from polyenes having a carbon number of 5 to 20 and having a plurality of vinyl and / or vinylidene groups in the molecule, and the content of vinyl and / or vinylidene groups derived from the aromatic polyene unit is 1.5 to less than 20 in terms of number average molecular weight.
[0030] (4) The olefin is one or more selected from olefins having 2 to 20 carbon atoms, and the total of the olefin monomer units, the aromatic vinyl compound monomer units and the aromatic polyene monomer units is 100% by mass.
[0031] Effects of the Invention
[0032] The curable composition of the present invention has properties as a thermoplastic resin. In addition, a cured product obtained by curing the curable composition has excellent low dielectric properties and high mechanical strength (elastic modulus, etc.) at room temperature and high temperature. DETAILED DESCRIPTION
[0033] Hereinafter, further detailed description will be given. In this specification, olefin-aromatic vinyl compound-aromatic polyene copolymer is sometimes referred to as copolymer. Unless otherwise specified, the numerical range in this specification includes its upper limit and lower limit. In this specification, sheet also includes the concept of film. In addition, in this specification, even if it is recorded as film, it also represents the same meaning as sheet. In addition, in this specification, solidified body is the same meaning as solidified body. In this specification, content is sometimes also referred to as content.
[0034] <Composition>
[0035] In this specification, the composition (curable composition) is sometimes described as a resin composition or a curable resin composition. The composition of the present invention comprises the above-mentioned olefin-aromatic vinyl compound-aromatic polyene copolymer having a composition and a molecular weight range within the above-mentioned specific range. In addition, the composition further comprises a predetermined amount of one or more "additive resins". Furthermore, the composition may further comprise the "monomer" and "curing agent" described later.
[0036] <Olefin-aromatic vinyl compound-aromatic polyene copolymer>
[0037] The conventional method for producing an olefin-aromatic vinyl compound-aromatic polyene copolymer that can be used in the present invention is described in, for example, Japanese Patent Application Publication No. 2009-161743, Japanese Patent Application Publication No. 2010-280771, and International Publication No. WO00 / 37517. The olefin-aromatic vinyl compound-aromatic polyene copolymer (hereinafter, in this specification, sometimes simply referred to as "copolymer") satisfies all of the following conditions (1) to (4).
[0038] (1) The number average molecular weight of the copolymer is 5,000 to 100,000, preferably 20,000 to 100,000, and more preferably 30,000 to 100,000.
[0039] (2) The aromatic vinyl compound monomer is an aromatic vinyl compound having 8 to 20 carbon atoms, and the content of the aromatic vinyl compound monomer unit is 0% by mass to 70% by mass.
[0040] (3) The aromatic polyene is one or more polyenes having a carbon number of 5 to 20 and having a plurality of vinyl and / or vinylidene groups in the molecule, and the content of vinyl and / or vinylidene groups derived from the aromatic polyene units is 1.5 to 20, preferably 1.5 to 7, and more preferably 2 to 5, in terms of number average molecular weight.
[0041] (4) The olefin is one or more selected from olefins having 2 to 20 carbon atoms, and the total of the olefin monomer units, the aromatic vinyl compound monomer units and the aromatic polyene monomer units is 100% by mass.
[0042] The olefin-aromatic vinyl compound-aromatic polyene copolymer can be obtained by copolymerizing each monomer of an olefin, an aromatic vinyl compound, and an aromatic polyene.
[0043] The so-called olefin monomer is one or more selected from alpha olefins with a carbon number of 2 to 20 and cyclic olefins with a carbon number of 5 to 20, and is a compound substantially free of oxygen, nitrogen, and halogen and composed of carbon and hydrogen. As alpha olefins with a carbon number of 2 to 20, for example, ethylene, propylene, 1-butene, 1-hexene, 1-octene, 1-decene, 1-dodecene, 4-methyl-1-pentene, and 3,5,5-trimethyl-1-hexene can be exemplified. As cyclic olefins with a carbon number of 5 to 20, norbornene and cyclopentene can be exemplified. As an olefin, it is preferably a combination of alpha olefins other than ethylene and cyclic olefins, or ethylene alone. When the mass ratio of ethylene alone or alpha olefins / ethylene other than ethylene is less than 1 / 7, more preferably less than 1 / 10, it is preferred that the peel strength of the obtained solidified body and copper foil and copper wiring can be improved. It is further preferred that the content of the alpha olefin monomer unit other than ethylene contained in the copolymer is 6% by mass or less, and most preferably 4% by mass or less, or the olefin is ethylene alone. In this case, the peel strength with copper foil and copper wiring can be further improved, which is more preferred. In addition, with regard to the preferred combination of ethylene and alpha olefins other than ethylene, the glass transition temperature of the ethylene-alpha olefin-aromatic vinyl compound-aromatic polyene chain of the final solidified body can be freely adjusted in the range of approximately -60°C to -5°C, preferably -50°C to -10°C, depending on the type and content of the alpha olefin.
[0044] The aromatic vinyl compound monomer is an aromatic vinyl compound having 8 to 20 carbon atoms, and examples thereof include styrene, p-methylstyrene, p-isobutylstyrene, various vinylnaphthalenes, and various vinylanthracenes.
[0045] As an aromatic polyene monomer, it is a polyene with a carbon number of 5 to 20 having multiple vinyl groups and / or vinylidene groups in its molecule, preferably a polyene with a carbon number of 8 to 20. As an aromatic polyene monomer, it is preferably a polyene with a carbon number of 8 to 20 having multiple vinyl groups in the molecule, and further preferably various divinylbenzenes at ortho, meta, and para positions or mixtures thereof, divinylnaphthalene, divinylanthracene, p-2-propylene styrene, p-3-butylene styrene, etc. having an aromatic vinyl structure and substantially free of oxygen, nitrogen, halogen and composed of carbon and hydrogen. In addition, difunctional aromatic vinyl compounds described in Japanese Patent Publication No. 2004-087639, such as 1,2-bis(vinylphenyl)ethane (abbreviated as: BVPE), can also be used. Among them, various divinylbenzenes at ortho, meta, and para positions, or mixtures thereof are preferably used, and a mixture of m-divinylbenzene and p-divinylbenzene is most preferably used. In this specification, these divinylbenzenes are described as divinylbenzenes. When divinylbenzenes are used as the aromatic polyene, curing efficiency is high and curing is easy during curing treatment, which is preferred.
[0046] As the above olefin, aromatic vinyl compound, each monomer of aromatic polyene, it is also possible to include in addition the olefin containing polar groups such as oxygen atoms, nitrogen atoms, aromatic vinyl compounds containing oxygen atoms, nitrogen atoms, etc., or aromatic polyene containing oxygen atoms, nitrogen atoms, etc., the gross mass of these monomers containing polar groups is preferably below 10 mass % of the gross mass of the composition, more preferably below 3 mass %, most preferably not including the monomer containing polar groups. By making it below 10 mass %, it is possible to improve the low dielectric properties (low dielectric constant / low dielectric loss) of the cured body obtained by curing the composition.
[0047] The number average molecular weight of the copolymer is 5000 to 100,000, preferably 20,000 to 100,000, more preferably 30,000 to 100,000. By making it such a range, even if the added resin is added in an uncured state, it is not easy to be sticky, and the effect of improving thermoplasticity can be obtained. In addition, it is easy to give good physical properties such as high breaking strength and high elongation at break to the finally obtained solidified body. When the number average molecular weight is less than 5000, the mechanical properties of the composition in the uncured stage are low, and the adhesiveness is high. Therefore, the composition is sometimes difficult to be molded as a thermoplastic resin. If the number average molecular weight is higher than 100,000, there is a situation where the molding processability is reduced. The content of the aromatic vinyl compound monomer unit contained in the copolymer is 0 mass % to 70 mass %, preferably 10 mass % to 60 mass %, more preferably 10 mass % to 55 mass %. When the content of the aromatic vinyl compound monomer unit is greater than 70 mass %, the glass transition temperature of the solidified body of the finally obtained composition is near room temperature, and there is a situation where the toughness and elongation at low temperature are reduced. If the content of the aromatic vinyl compound monomer unit is 10% by mass or more, the aromaticity of the copolymer is improved, the affinity with the flame retardant and the filler becomes good, the flame retardant does not ooze out, and the filler can be filled. In addition, when the content of the aromatic vinyl compound monomer unit is 10% by mass or more, a cured body of the composition having high peel strength with copper foil and copper wiring can be obtained.
[0048] In the copolymer, the content of vinyl and / or vinylidene groups derived from the aromatic polyene unit is 1.5 or more and less than 20, preferably 2 or more and less than 20, and more preferably 3 or more and less than 10, in terms of number average molecular weight. Hereinafter, the content of vinyl and / or vinylidene groups is sometimes collectively referred to as "vinyl content". When it is less than 1.5, the crosslinking efficiency is low, and it is difficult to obtain a cured product with sufficient crosslinking density. If the vinyl content is increased, it is easy to improve the mechanical properties of the cured product finally obtained at room temperature and at high temperature. With regard to the vinyl content derived from the aromatic polyene unit in the copolymer in terms of number average molecular weight, it can be calculated by dividing the number average molecular weight (Mn) calculated by the GPC (gel permeation chromatography) method known to those skilled in the art by the standard polystyrene conversion and the number average molecular weight (Mn) calculated by the GPC (gel permeation chromatography) method known to those skilled in the art by the standard polystyrene conversion. 1 The vinyl content and vinylidene content derived from the aromatic polyene unit obtained by H-NMR measurement are compared. 1Comparison of the intensity of each peak area obtained by H-NMR measurement, the vinyl content derived from the aromatic polyene unit in the copolymer is 0.095 mass %, and the number average molecular weight based on standard polystyrene conversion measured by GPC is 68,000. The molecular weight of the vinyl derived from the aromatic polyene unit in the number average molecular weight is the product of these, i.e., 64.8. This molecular weight is divided by the formula weight of the vinyl, 27, to obtain 2.4. That is, the vinyl content derived from the aromatic polyene unit in the copolymer in terms of number average molecular weight is 2.4. 1 The attribution of the peaks obtained by H-NMR measurement is known in the literature. 1 The method of determining the composition of the copolymer by comparing the peak areas obtained by H-NMR measurement is also known. 1 The content of divinylbenzene units in the copolymer was determined by 1H-NMR measurement. That is, based on the content of vinyl groups derived from divinylbenzene units, the content of divinylbenzene units was determined assuming that one vinyl group was derived from one divinylbenzene unit in the copolymer.
[0049] In this copolymer, the preferred olefin monomer unit content is 30% by mass or more, and particularly preferably 45% by mass or more. The total of the above-mentioned olefin monomer unit, aromatic vinyl compound monomer unit and aromatic polyene monomer unit is 100% by mass. When the olefin monomer unit content is 30% by mass or more, the toughness (elongation) of the finally obtained cured product is improved, and no fracture during curing, reduction in the impact resistance of the cured product, or fracture of the cured product in a thermal cycle test will occur. In this copolymer, the preferred olefin monomer unit content is 90% by mass or less.
[0050] Among the copolymers, preferred are olefin-aromatic polyene copolymers not containing aromatic vinyl compound monomer units, and specific examples thereof include ethylene-divinylbenzene copolymers, ethylene-propylene-divinylbenzene copolymers, ethylene-1-butene-divinylbenzene copolymers, ethylene-1-hexene-divinylbenzene copolymers, and ethylene-1-octene-divinylbenzene copolymers.
[0051] Examples of the olefin-aromatic vinyl compound-aromatic polyene copolymer containing an aromatic vinyl compound monomer unit in the copolymer include ethylene-styrene-divinylbenzene copolymer, ethylene-propylene-styrene-divinylbenzene copolymer, ethylene-1-hexene-styrene-divinylbenzene copolymer, and ethylene-1-octene-styrene-divinylbenzene copolymer.
[0052] <Adding resin>
[0053] The composition of the present invention may contain one or more resins selected from hydrocarbon elastomers, polyphenylene ethers, olefin-aromatic vinyl compound-aromatic polyene copolymer oligomers, and aromatic polyene resins (abbreviated as "added resins" in this specification) preferably in a total of 1 to 500 parts by mass, and more preferably in a total of 1 to 300 parts by mass, relative to 100 parts by mass of the copolymer contained. As the added resin, polyphenylene ether and / or hydrocarbon elastomers can be particularly preferably used. Among hydrocarbon elastomers, conjugated diene polymers are preferred. Among conjugated diene polymers, 1,2-polybutadiene is preferred. By using polyphenylene ether and / or 1,2-polybutadiene, the amount of monomer used can be reduced. For example, even if no monomer is used, a preferred cured product of the present invention can be obtained.
[0054] <Hydrocarbon elastomer>
[0055] The amount of hydrocarbon elastomer used in the composition of the present invention is preferably 1 to 500 parts by mass, more preferably 1 to 200 parts by mass, relative to 100 parts by mass of the copolymer. The hydrocarbon elastomer that can be preferably used in the composition of the present invention is one or more elastomers selected from ethylene-based, propylene-based elastomers, conjugated diene polymers, aromatic vinyl compound-conjugated diene block copolymers or random copolymers, and their hydrogenates (hydrogenated products). The number average molecular weight of the hydrocarbon elastomer is 1000 or more, more preferably 2000 or more, and most preferably 30,000 or more. The number average molecular weight of the hydrocarbon elastomer is preferably 80,000 or less, more preferably 60,000 or less.
[0056] Examples of the ethylene-based elastomer include ethylene-α-olefin copolymers such as ethylene-octene copolymers and ethylene-1-hexene copolymers, EPR, and EPDM. Examples of the propylene-based elastomer include propylene-α-olefin copolymers such as random polypropylene, low stereoregularity polypropylene, and propylene-1-butene copolymers.
[0057] As conjugated diene polymers, polybutadiene and 1,2-polybutadiene can be cited. As block copolymers or random copolymers of aromatic vinyl compounds-conjugated dienes, and their hydrogenated products (hydrogenated products), SBS, SIS, SEBS, SEPS, SEEPS, SEEBS, etc. can be exemplified. 1,2-polybutadiene that can be preferably used can be obtained as a product of JSR Corporation, for example, and can also be obtained from Nippon Soda Co., Ltd. as liquid polybutadiene: product name B-1000, 2000, 3000. In addition, as a copolymer containing a 1,2-polybutadiene structure that can be preferably used, "Ricon100" of TOTAL CRAYVALLEY can be exemplified. In particular, when one or more resins selected from these hydrocarbon elastomers are liquid (about 300,000 mPa·S or less) at room temperature (25°C), from the viewpoint of the handleability and molding processability (handleability as a thermoplastic resin) of the composition of the present invention in an uncured state, the amount used is preferably in the range of 1 to 30 parts by mass, and particularly preferably in the range of 1 to 20 parts by mass, relative to 100 parts by mass of the copolymer.
[0058] <Polyphenylene ether>
[0059] As polyphenylene ether, commercially available known polyphenylene ether can be used. The number average molecular weight of polyphenylene ether is arbitrary. When considering the molding processability of the composition, the number average molecular weight is preferably less than 10,000, and most preferably less than 5,000. The number average molecular weight is preferably more than 500, and most preferably more than 1,000. In addition, when added for the purpose of curing of the composition of the present invention, it is preferred that the molecular end is modified, and / or it is preferred to have multiple functional groups in one molecule. As functional groups, functional groups such as allyl, vinyl, and epoxy groups can be cited, and free radical polymerizable functional groups are most preferably free radical polymerizable functional groups, such as vinyl, especially (meth) acrylic acid groups, and aromatic vinyl. That is, in the composition of the present invention, it is particularly preferred that the two ends of the molecular chain are modified by free radical polymerizable functional groups. As such polyphenylene ether, Noryl (trademark) SA9000 of SABIC can be cited, and it is particularly preferred that a difunctional polyphenylene ether oligomer (OPE-2St) manufactured by Mitsubishi Gas Chemical Co., Ltd. can be used. The usage-amount of the polyphenylene ether used for the composition of this invention is preferably 1-200 mass parts with respect to 100 mass parts of copolymers, and more preferably 10-100 mass parts.
[0060] <Olefin-aromatic vinyl compound-aromatic polyene copolymer oligomer>
[0061] In addition, an olefin-aromatic vinyl compound-aromatic polyene copolymer oligomer may be added to the cured product of the present invention, and an olefin-aromatic vinyl compound-aromatic polyene copolymer oligomer satisfying the following conditions (1A) to (4A) may be particularly preferably added. The olefin-aromatic vinyl compound-aromatic polyene copolymer oligomer referred to herein does not include the above-mentioned olefin-aromatic vinyl compound-aromatic polyene copolymer satisfying the above-mentioned conditions (1) to (4).
[0062] (1A) The number average molecular weight of the copolymerized oligomer is 500 or more and less than 5,000.
[0063] (2A) The aromatic vinyl compound monomer is an aromatic vinyl compound having 8 to 20 carbon atoms, and the content of the aromatic vinyl compound monomer unit is 0% by mass to 70% by mass.
[0064] (3A) The aromatic polyene is one or more selected from polyenes having 5 to 20 carbon atoms and having a plurality of vinyl groups and / or vinylidene groups in the molecule, and the vinyl content derived from the aromatic polyene unit is 1.5 or more in terms of number average molecular weight.
[0065] (4A) The olefin is one or more selected from olefins having 2 to 20 carbon atoms, and the olefin monomer unit content is 30% by mass or more, and the total of the olefin monomer units, aromatic vinyl compound monomer units and aromatic polyene monomer units is 100% by mass.
[0066] The amount of the olefin-aromatic vinyl compound-aromatic polyene copolymer oligomer used in the composition of the present invention is preferably in the range of 1 to 49 parts by mass relative to 100 parts by mass of the copolymer. In addition, from the viewpoint of the operability and molding processability of the composition of the present invention in an uncured state, it is preferably in the range of 1 to 30 parts by mass, and particularly preferably in the range of 1 to 20 parts by mass relative to 100 parts by mass of the copolymer.
[0067] The definitions and methods of determining olefins, aromatic vinyl compounds, aromatic polyenes, number average molecular weights, and vinyl content are the same as those of the above-mentioned copolymers. The method of determining the number average molecular weight of the copolymerized oligomers is as follows. With regard to molecular weight, the number average molecular weight (Mn) converted to standard polystyrene is determined using GPC (gel permeation chromatography). The determination is performed under the following conditions.
[0068] (When the number average molecular weight is 1000 or more)
[0069] Chromatographic columns: Two TSK-GEL MultiporeHXL-M ×300 mm (manufactured by Tosoh Corporation) were connected in series and used.
[0070] Column temperature: 40°C
[0071] Solvent: THF
[0072] Liquid delivery flow: 1.0ml / min.
[0073] Detector: RI detector (differential refractive index detector)
[0074] (When the number average molecular weight is less than 1000)
[0075] Chromatographic column: 1 TSKgelG3000HXL ×300mm, 1 piece of TSKgelG2000HXL ×300mm, 4 pieces of TSKgelG1000HXL ×300 mm (manufactured by Tosoh Corporation) were connected in series and used.
[0076] Column temperature: 40°C
[0077] Solvent: THF
[0078] Liquid delivery flow: 0.5ml / min.
[0079] Detector: RI detector
[0080] <Aromatic polyene resin>
[0081] Aromatic polyene resins include divinylbenzene reactive multi-branch copolymers (PDV) manufactured by NIPPON STEEL Chemical & Material Co. Such PDVs are described in, for example, the document "Synthesis of multifunctional aromatic vinyl copolymers and development of novel IPN-type low dielectric loss materials using the same" (Kawabe Masanori et al., Journal of Japan Institute of Electronics Packaging, p125, Vol. 12 No. 2 (2009)). In addition, aromatic polyene resins include aromatic polyene polymer resins having the above-mentioned aromatic polyene monomers as main structural units.
[0082] <Curing agent>
[0083] As the curing agent that can be used in the curable composition of the present invention, known curing agents that can be used in the polymerization or curing of aromatic polyenes and aromatic vinyl compounds can be used. Such curing agents include free radical polymerization initiators, cationic polymerization initiators, and anionic polymerization initiators. Preferably, free radical polymerization initiators can be used. Organic peroxide-based (peroxide) and azo-based polymerization initiators are preferred, and they can be freely selected according to the application and conditions. A catalogue recording examples of organic peroxides can be downloaded from the homepage of NOF Corporation, for example
[0084] https: / / www.nof.co.jp / business / chemical / product01a.html
[0085] https: / / www.nof.co.jp / business / chemical / product01b.html
[0086] https: / / www.nof.co.jp / business / chemical / product01c.html.
[0087] In addition, examples of organic peroxides are also recorded in the catalogs of Wako Pure Chemical Industries, Ltd. and Tokyo Chemical Industry Co., Ltd. The curing agent used in the present invention can be obtained from these companies. In addition, known photopolymerization initiators using light, ultraviolet rays, and radiation can also be used as curing agents. As curing agents using photopolymerization initiators, light free radical polymerization initiators, photocationic polymerization initiators, or photoanionic polymerization initiators can be cited. Such photopolymerization initiators can be obtained, for example, from Tokyo Chemical Industry Co., Ltd. In addition, curing based on radiation or electron beams themselves can also be used. In addition, crosslinking and curing can also be performed by thermal polymerization of the raw materials contained without containing a curing agent.
[0088] The amount of the curing agent used is not particularly limited, and is generally preferably 0.01 to 10 parts by mass relative to 100 parts by mass of the composition. When using a curing agent such as an organic peroxide (peroxide) or an azo polymerization initiator, the curing treatment is performed at an appropriate temperature and time in consideration of its half-life. The conditions at this time can be selected according to the curing agent, and generally, a temperature range of about 50°C to 180°C is appropriate.
[0089] <Single body>
[0090] The amount of monomer that the composition of the present invention can contain is arbitrary, preferably 10 parts by mass or less relative to 100 parts by mass of the copolymer. It should be noted that the composition may not contain monomers in substance. When the monomer is 10 parts by mass or less, the uncured composition does not have viscosity, and molding processing as a thermoplastic resin becomes easy. In addition, when the content of the amount of monomer that is easy to volatilize is below a certain value, the odor of the uncured stage will not become a problem. In the case where a solvent is added to the composition and the product form is varnish-like, there is the following problem: when used, the monomer disappears with the evaporation of the solvent (solvent), and the substantial content of the monomer is easily reduced. In addition, in the case where the product form is an uncured sheet, if a certain amount of monomer is contained, the monomer content is not easy to change during storage. The molecular weight of the monomer that can be preferably used in the composition of the present invention is preferably less than 1000, and more preferably less than 500. The monomer that can be preferably used in the composition of the present invention is an aromatic vinyl compound monomer, an aromatic polyene monomer, and / or a polar monomer. As the monomer, it is preferred that a monomer that can be polymerized using a free radical polymerization initiator is used, and the above-mentioned aromatic vinyl compound and aromatic polyene are more preferred. In addition, BVPE (1,2-bis(vinylphenyl)ethane) recorded in Japanese Patent Publication No. 2003-212941 can also be preferably used. From the viewpoint of improving the mechanical strength (elastic modulus) of the cured body at high temperature, the aromatic polyene is preferably 1 mass part or more and 30 mass parts or less relative to 100 mass parts of the copolymer. In addition, for the purpose of imparting adhesion to other materials required as an insulating material or improving the crosslinking density, a relatively small amount of polar monomers can be used. As the above-mentioned polar monomer, various maleimides, bismaleimides, maleic anhydride, glycidyl (meth) acrylate, triallyl isocyanurate, tri(meth) acrylate isocyanurate, trimethylolpropane tri(meth) acrylate, etc. can be cited. Maleimides and bismaleimides that can be used in the present invention are described in, for example, International Publication No. WO2016 / 114287 and Japanese Patent Application Laid-Open No. 2008-291227, and can be purchased from, for example, Yamato Chemical Industry Co., Ltd. and Designer molecules Inc. From the viewpoints of solubility in organic solvents, high-frequency characteristics, high adhesion to conductors, and prepreg formability, these maleimide group-containing compounds are preferably bismaleimides.
[0091] The bismaleimides are preferably bismaleimides represented by the following formula (B-1).
[0092] Formula (B-1)
[0093] [Chemical formula 1]
[0094]
[0095] In formula (B-1), R represents an alkylene group having 5 or more carbon atoms, and L represents a single bond or a divalent linking group. R and L may each independently have a substituent. In addition, the maleimide represented by formula (B-1) is preferably represented by the following formula (B-2).
[0096] Formula (B-2)
[0097] [Chemical formula 2]
[0098]
[0099] In formula (B-2), R' independently represents an alkylene group having 5 or more carbon atoms which may have a substituent, and A independently represents an alkylene group having 5 or more carbon atoms which may have a substituent or a divalent group having an aromatic ring which may have a substituent. n represents an integer of 1 to 10.
[0100] Examples of maleimides represented by formula (B-2) include compounds represented by the following formula (B-3): wherein n represents an integer of 1 to 10. Examples of compounds represented by formula (B-3) include BMI-1500 manufactured by Designer Molecules Inc. (n average value = 1.3).
[0101] Formula (B-3)
[0102] [Chemical formula 3]
[0103]
[0104] Bismaleimides can be used as polyaminobismaleimide compounds. Polyaminobismaleimide compounds can be obtained, for example, by the following method: a compound having two maleimide groups at the end is subjected to a Michael addition reaction with an aromatic diamine compound having two primary amino groups in the molecule. In the case where a high crosslinking efficiency is desired to be obtained with a small amount of addition, it is preferred to use a polar monomer having a multifunctional group of more than two functional groups, and examples thereof include bismaleimides, triallyl isocyanurate (TAIC), and trimethylolpropane tri(meth)acrylate. The amount of polar monomer that the composition can contain is in the range of 0.1 to 10 parts by mass, preferably 0.1 to 5 parts by mass, relative to 100 parts by mass of the copolymer. By using less than 10 parts by mass, the dielectric constant and dielectric loss tangent of the obtained cured body are reduced. For example, the dielectric constant becomes less than 3.0, and the dielectric loss tangent becomes less than 0.005.
[0105] <Solvent>
[0106] A suitable solvent may be added to the composition of the present invention as needed. The solvent is used to adjust the viscosity and fluidity of the composition. As a solvent, a volatile solvent is preferred, for example, cyclohexane, toluene, ethylbenzene, acetone, isopropanol, etc. can be used. In addition, from the perspective of the molding processability and operation of the composition before curing as a thermoplastic resin, the amount used is preferably 10 parts by mass or less relative to 100 parts by mass of the copolymer of the present invention. In addition, from the perspective of removal during and after curing, it is more preferred that no solvent is substantially used. The so-called substantially no use means preferably 5 parts by mass or less, more preferably 1 part by mass or less, and most preferably 0 parts by mass. In addition, when used in the form of a varnish, it is preferred to add a suitable solvent to the composition of the present invention. The solvent is used to adjust the viscosity and fluidity of the composition as a varnish. As a solvent, when the boiling point at atmospheric pressure is high, that is, the volatility is low, the thickness of the coated film becomes uniform, so a solvent with a boiling point above a certain degree is preferred. The preferred boiling point is about 100°C or more at atmospheric pressure, preferably 130°C or more and 300°C or less. As a solvent suitable for such a varnish, toluene, xylene, mesitylene, ethylbenzene, limonene, ethylene glycol methyl ether acetate, ethylene glycol monoethyl ether acetate, ethylene glycol monobutyl ether, etc. can be used. In addition, the amount used is preferably in the range of 10 to 2000 parts by mass relative to 100 parts by mass of the composition of the present invention.
[0107] <Composition>
[0108] The composition of the present invention may further include one or more selected from fillers, flame retardants, and surface modifiers relative to the above composition. In order to be able to become a matrix of a cured body and to make the filling property of other materials excellent during curing, the composition of the present invention includes one or more selected from these fillers, flame retardants, and surface modifiers, and even after curing, the cured body is likely to show impact resistance and toughness.
[0109] <Filling agent>
[0110] In addition, known inorganic or organic fillers can also be added as needed. These fillers are added for the purpose of controlling thermal expansion coefficient, controlling thermal conductivity, and cheapening, and their usage amount is arbitrary according to the different purposes. The composition of the present invention can especially contain a large amount of inorganic fillers, and relative to 100 parts by mass of the copolymer, its usable amount can reach a maximum of 2000 parts by mass. Especially when adding inorganic fillers, it is preferred to use known surface modifiers such as silane coupling agents. Especially as one of the purposes of the present invention, i.e., when the composition with low dielectric constant and excellent low dielectric loss is the purpose, as inorganic fillers, boron nitride (BN) and / or silicon dioxide are preferred, preferably silicon dioxide. In silicon dioxide, fused silica is preferred. Due to the fact that the dielectric constant may become higher when adding a large amount of coordination, therefore, from the viewpoint of low dielectric properties, it is preferred to use a filler less than 500 parts by mass relative to 100 parts by mass of the copolymer, and it is further preferred to use a filler less than 400 parts by mass. Furthermore, in order to improve and enhance the low dielectric properties (low dielectric constant, low dielectric loss), a hollow filler or a filler with many voids may be added.
[0111] In addition, it is also possible to replace inorganic fillers and use organic fillers such as high molecular weight or ultra-high molecular weight polyethylene. From the viewpoint of heat resistance, organic fillers are preferably crosslinked themselves, preferably used in the state of particulate or powder. These organic fillers can suppress the rise of dielectric constant, dielectric loss tangent. Relative to 100 mass parts of copolymers, the usage amount of filler is most preferably more than 1 mass part and less than 400 mass parts.
[0112] On the other hand, by mixing and dispersing a high dielectric constant insulator filler having a dielectric constant of preferably 3 to 10,000 (more preferably 5 to 10,000) at 1 GHz in the composition of the present invention, it is possible to produce an insulating solid body having a high dielectric constant insulating layer having a dielectric constant of preferably 3.1 to 20 while suppressing the increase in dielectric loss tangent (dielectric loss). By increasing the dielectric constant of the film formed by the insulating solid body, it is possible to achieve miniaturization of circuits and high capacitance of capacitors, which can contribute to the miniaturization of high-frequency electrical components. High dielectric constant, low dielectric loss tangent insulating layers are suitable for capacitors, inductors for resonant circuits, filters, antennas, and the like. As the high dielectric constant insulator filler used in the present invention, inorganic fillers or metal particles subjected to insulation treatment can be cited. Specific examples are known high dielectric constant inorganic fillers such as barium titanate and strontium titanate, and other examples are specifically described in, for example, Japanese Patent Publication No. 2004-087639.
[0113] <Flame retardant>
[0114] The composition of the present invention can use known flame retardants. From the viewpoint of maintaining low dielectric constant and low dielectric loss tangent, preferred flame retardants are known organic phosphorus-based flame retardants such as phosphates or their condensates, known bromine-based flame retardants, and red phosphorus. In particular, among phosphates, compounds having multiple xylene groups in the molecule are preferred from the viewpoint of flame retardancy and low dielectric loss tangent.
[0115] Furthermore, in addition to the flame retardant, antimony compounds such as antimony trioxide, antimony tetroxide, antimony pentoxide, sodium antimonate, or nitrogen-containing compounds such as melamine, triallyl-1,3,5-triazine-2,3,4-(1H,3H,5H)-trione, and 2,4,6-triallyloxy-1,3,5-triazine may be added as flame retardant aids. The total amount of these flame retardants and flame retardant aids is usually preferably 1 to 100 parts by mass relative to 100 parts by mass of the composition. In addition, 30 to 200 parts by mass of the above-mentioned polyphenylene ether (PPE)-based resin with low dielectric constant and excellent flame retardancy may be added relative to 100 parts by mass of the flame retardant.
[0116] <Surface modifier>
[0117] The composition of the present invention may contain various surface modifiers for the purpose of improving the adhesion with fillers, copper plates, and wiring. The amount of the surface modifier used is preferably 0.01 to 10 parts by mass, more preferably 0.1 to 5 parts by mass, relative to 100 parts by mass of the composition of the present invention other than the surface modifier. As the surface modifier, various silane coupling agents, titanate coupling agents, etc. can be cited. Various silane coupling agents and titanate coupling agents can use one or more.
[0118] In the present invention, by changing the proportion of the copolymer, monomer, added resin, and solvent added as needed in the composition within the above range, or further by changing the proportion of the flame retardant, filler, and surface modifier, the fluidization temperature of the curable resin or composition can be adjusted according to its purpose and molding method. Specifically, the composition of the present invention can take the form of a product such as "thermoplastic composition", "semi-cured state (B stage sheet, etc.)", and "varnish".
[0119] The composition of the present invention is obtained by mixing, dissolving or melting the copolymer and the curing agent, and one or more selected from monomers, solvents, added resins, fillers, flame retardants and surface modifiers as required, as described above. The mixing, dissolving and melting method can be any known method.
[0120] <Thermoplastic composition and molded article>
[0121] Composition of the present invention uses the copolymer of the molecular weight of the scope with more than certain value, and contains the above-mentioned added resin of regulation, therefore shows the character of thermoplastic resin.Therefore, by under the condition of not causing crosslinking, utilizing the known molding processing method as thermoplastic resin, can be shaped into the shape such as sheet, tube, strip, pellet with substantially uncured state, then can make it crosslinked (curing).In this specification, sheet also includes the concept of film.In addition, in this specification, even if be recorded as film, also include the concept of sheet.
[0122] In addition, the preferred embodiment of the composition is as follows. When a certain proportion or more of one or more resins selected from the above-mentioned hydrocarbon elastomer, polyphenylene ether, olefin-aromatic vinyl compound-aromatic polyene copolymer oligomer, or aromatic polyene resin is included as an added resin (excluding liquid resins at room temperature), it is also easy to perform molding processing as a thermoplastic resin in an uncured state. Specifically, it is preferred that the above-mentioned hydrocarbon elastomer (excluding liquid resins) and / or polyphenylene ether can be added in a range of 30 to 200 parts by mass relative to 100 parts by mass of the copolymer. In addition, when the added resin is liquid at room temperature, it can be added in a range of preferably 1 to 30 parts by mass, particularly preferably 1 to 20 parts by mass relative to 100 parts by mass of the copolymer. The amount of the monomer that can be used in the thermoplastic composition is preferably 10 parts by mass or less relative to 100 parts by mass of the copolymer. The number average molecular weight of the copolymer used is 5000 to 100,000, preferably 20,000 to 100,000, and more preferably 30,000 to 100,000. The above thermoplastic composition can be preformed into various shapes such as sheets at a temperature below the action temperature of the curing agent by utilizing its thermoplasticity, and can be laminated and combined with a semiconductor element, wiring, or substrate as required, and then cured and bonded by heating.
[0123] The composition of the present invention can also be provided in the form of the following sheet, which is obtained by molding the composition after heating and melting at a temperature below the action temperature or decomposition temperature of the curing agent using a known method. The molding of the sheet can be extrusion molding based on a T die, a double-roll mill can also be used, or it can be extruded and laminated on a substrate film. In this case, the composition, the mass ratio of copolymer / monomer, or the selection and adjustment of solvent, added resin, and flame retardant are carried out in a manner that melts below the action temperature or decomposition temperature of the curing agent and becomes solid near room temperature. The sheet at this time is substantially in an uncured state. Then, it undergoes various processing and assembly steps, and is finally treated with a temperature and time above the action temperature or decomposition temperature of the curing agent to fully cure it. Such a method is a common technology used for the cross-linked sealant sheet of the ethylene-vinyl acetate resin system of a solar cell (solar power generation device).
[0124] <Moldings in semi-cured state (B-stage sheets, etc.)>
[0125] In addition, the composition of the present invention can also be made into a partially cross-linked state, such as a molded body, such as a sheet, a tube, etc., in a semi-cured state (so-called B stage state) by reacting a part of the curing agent contained therein. For example, it can be semi-cured by adopting a variety of curing agents and / or curing conditions with different curing temperatures, controlling melt viscosity and fluidity, and making a B stage state. That is, it is also possible to shape the curable resin and the composition into a B stage sheet that is easy to operate by curing (partially cured) in the first stage, stack it on an electronic device, a substrate, and crimp it, and then perform curing (completely cured) in the second stage to make the final shape. In this case, the composition of the composition, i.e., the mass ratio of the copolymer / monomer, can be selected, a solvent, a resin, a flame retardant are added as needed, and then the composition containing a curing agent such as a peroxide is partially cured, adjusted to a sheet shape (B stage state), and the equipment is molded and assembled, and heated under pressure to make it completely cured. As a method for partially curing the composition, a known method can be used, for example, the following method: using peroxides with different decomposition temperatures, treating them at a temperature where only one of them actually works for a specified time to obtain a semi-cured sheet, and finally treating them at a temperature where all curing agents work for a sufficient time to completely cure them.
[0126] In addition, the molded body may be a sheet. The sheet may be uncured (semi-cured) to the extent that the sheet shape can be maintained, or may be a fully cured sheet. The degree of curing of the composition can be quantitatively determined using a known dynamic viscoelasticity determination method (DMA, Dynamic Mechanical Analysis).
[0127] <Varnish-like composition and molded article thereof>
[0128] The composition of the present invention can also be made into a viscous liquid varnish by its composition and mixing ratio. For example, it can be made into a varnish by using a sufficient amount of solvent and / or by using an appropriate amount of liquid monomer. In particular, when used as a varnish, it is preferred to add a suitable solvent to the composition of the present invention. The solvent is used to adjust the viscosity and fluidity of the composition as a varnish. As a solvent, when the boiling point at atmospheric pressure is high, that is, the volatility is low, it has the advantage that the thickness of the coated film becomes uniform, so a solvent with a boiling point above a certain degree is preferred. The preferred boiling point is about 100°C or more at atmospheric pressure, preferably 130°C or more and 300°C or less. As a solvent suitable for such a varnish, xylene, mesitylene, ethylbenzene, limonene, ethylene glycol methyl ether acetate, ethylene glycol monoethyl ether acetate, ethylene glycol monobutyl ether, etc. can be used. In addition, relative to 100 parts by mass of the composition of the present invention, its usage amount is preferably in the range of 10 to 2000 parts by mass. The varnish-like composition of the present invention can also be made using a polymerization liquid containing the copolymer of the present invention obtained by polymerization. For example, the polymerization solution may be concentrated or residual monomers may be removed, or a solvent, other resin components, various additives, etc. may be added as necessary to adjust the component concentrations, solution viscosity, etc. for production.
[0129] The varnish can be applied to or impregnated into a substrate, and the solvent can be removed by drying, etc. to form an uncured or semi-cured molded body. Usually, the molded body has a sheet, film, or tape form.
[0130] <Curing>
[0131] The composition can be cured by a known method with reference to the curing conditions (temperature, time, pressure) of the contained curing agent. When the curing agent used is a peroxide, the curing conditions can be determined with reference to the half-life temperature disclosed for each peroxide.
[0132] <Cured body obtained from the composition>
[0133] The dielectric constant of the cured product obtained from the composition of the present invention is 3.0 or less and 2.0 or more at 10 GHz, preferably 2.8 or less and 2.0 or more, and particularly preferably 2.5 or less and 2.0 or more. The dielectric loss tangent is 0.005 or less and 0.0003 or more, preferably 0.003 or less and 0.0005 or more. These dielectric constants and dielectric loss tangents can be obtained by any method known to those skilled in the art, for example, by a resonator method (resonant cavity perturbation method, balanced circular plate resonator method). In addition, the volume resistivity of the cured product obtained is preferably 1×10 15Ω·cm or more. These values are preferred values for electrical insulating materials for high frequencies such as 3 GHz or more. Since the copolymer used in the composition of the present invention is relatively soft and rich in tensile elongation, the cured body obtained from the composition using the copolymer can have the following characteristics: it shows sufficient mechanical properties, is relatively soft and has high impact resistance, and can follow the thermal expansion of the substrate. That is, the tensile modulus of the cured body of the present invention measured at room temperature (23°C) is less than 3GPa and is greater than 3MPa, preferably greater than 5MPa. In addition, especially when a large amount of fillers are added, the tensile modulus of elasticity sometimes takes a value of more than 3GPa and less than 20GPa. In addition, the tensile breaking strength is preferably less than 50MPa and more than 3MPa, more preferably more than 5MPa, and the tensile breaking elongation is preferably more than 30% and less than 300%, more preferably more than 50% and less than 250%. In addition, especially when a large amount of fillers are added, the tensile breaking elongation sometimes takes a value of less than 30%. The cured body of the composition of the present invention can have sufficient heat resistance for practical use. Specifically, from the perspective of practicality, the storage elastic modulus of the cured product of the composition of the present invention at 300°C can be 5×10 5 Pa or more, preferably 1×10 6 Pa or more. Those skilled in the art can refer to the information recorded in this specification and known materials to determine the combination of the composition having the above-mentioned physical property parameters and easily make a cured product. For the cured product obtained by the composition of the present invention, even under the condition that the aromatic polyene as a monomer or a component of a monomer in the composition is suppressed to below a certain proportion, it is also possible to show sufficient heat resistance and mechanical properties at high temperatures in practical use. As mentioned above, in order to maintain the molding processability as a thermoplastic resin even in an uncured state, it is also important to suppress the aromatic polyene as a monomer or a component of a monomer to below a certain proportion.
[0134] <General uses of the composition>
[0135] The composition of the present invention can be used as various insulating materials for wiring (preferably for wiring of high-frequency signals), such as cover layers, solder resists, buildup materials, interlayer insulating agents, bonding sheets, interlayer adhesives, and bump sheets for flip chip bonding machines. In addition, it can also be used as an electrical insulating layer or adhesive layer of a substrate or substrate such as a single-layer or multi-layer printed substrate, a flexible printed substrate, a CCL (copper clad laminate), or a FCCL (flexible copper clad laminate) substrate.
[0136] <Use of the composition as an uncured sheet or a partially cured sheet>
[0137] The uncured sheet or partially cured sheet of the composition of the present invention can be suitably used as an electrical insulating material for high frequency. For example, it can be suitably used as an insulating layer or adhesive layer for a build-up film, a bonding sheet, a cover layer sheet, a bump sheet for a flip chip bonding machine, or a substrate. It can also be used as a substitute for epoxy resin and silicone resin sheets used in the past, and a curing treatment is performed to form a cured insulating layer and a cured matrix phase with a low dielectric constant and low dielectric loss. The thickness of the sheet is usually 1 to 300 microns. The sheet can contain woven fabrics and non-woven fabrics such as glass cloth and ceramic fiber, or it can impregnate woven fabrics such as glass cloth and ceramic fiber, or it can form multiple layers with them. In addition, as an antenna cable for a mobile phone, etc., a soft and bendable wiring that is partially or completely insulated by this sheet can be used instead of the previous coaxial cable. For example, LCP (liquid crystal polymer), PPE sheet, fluorine resin, or polyimide resin can be used as a substrate, and the wiring can be covered and cured using the sheet or B-stage sheet (cover layer sheet) of the present invention, and bonded to the substrate to be used as an insulating material.
[0138] As for the multilayer wiring substrate with the solidified body obtained by using the composition of the present invention as an insulating layer, it is possible to become a wiring substrate with less dielectric loss and excellent high-frequency characteristics. In this case, in addition to low dielectric loss, the heat resistance of the solder, the flexibility and elongation and impact resistance to a certain extent of the stress caused by thermal cycle or thermal expansion difference become advantages. For example, the core material of the general resin plate, general laminated plate, etc., such as cloth, non-woven fabric, film material, ceramic substrate, glass substrate, epoxy resin, etc. formed by glass and quartz can be laminated and pressed with the conductor foil with the insulating layer formed by the solidified body, so as to make the wiring substrate. In addition, the slurry or solution containing the composition can also be applied to the core material, and dried and cured to form an insulating layer. The thickness of the insulating layer is generally 1 to 300 microns. Such a multilayer wiring substrate can also be used after multilayerization and integration.
[0139] The cured product obtained by curing the composition of the present invention, especially the varnish-like composition, as described above, can be suitably used as an electrical insulating material, especially as a bonding material, a surface coating, a covering layer, a solder resist, a build-up material, a bottom filler, a filling insulating agent, an interlayer insulating agent, an interlayer adhesive, or can be used in the form of a cured product as a printed substrate, a flexible printed substrate, an FCCL (flexible copper clad laminate) substrate, or as a cured product of a build-up film, a bonding sheet, a covering layer sheet, or a bump sheet for a flip chip bonding machine and used as an electrical insulating material (especially a high-frequency electrical insulating material).
[0140] From another perspective, the present invention is an electrical insulating material comprising an olefin-aromatic vinyl compound-aromatic polyene copolymer having a storage elastic modulus of 5×10 5The dielectric constant at 23° C. and 10 GHz is 2.5 or less and 2.0 or more, and the dielectric loss tangent is 0.003 or less and 0.0005 or more.
[0141] As for the uncured or semi-cured thermoplastic composition of the present invention, even if no adhesive coating or bonding treatment is particularly performed, it can be bonded to a metal foil (especially copper foil) for wiring by heating and pressurizing treatment. Here, copper foil is a concept of wiring including copper, and its shape is arbitrary. In particular, in the above-mentioned olefin-aromatic vinyl compound-aromatic polyene copolymer, it is preferred to use a copolymer with an aromatic vinyl compound content of 10% by mass or more, and / or by making the olefin alone ethylene, or the mass ratio of the olefin monomer component other than ethylene to the ethylene monomer component contained in the olefin is 1 / 7 or less, so that in the measurement in accordance with Japanese Industrial Standard (JIS) C6481: 1996, it is possible to provide a peel strength of 1N / mm or more. Furthermore, it is more preferred to provide a peel strength of 1.3N / mm or more. Further preferably, if in the above-mentioned copolymer, the olefin is ethylene alone, or the olefin monomer component other than ethylene is less than 1 / 10 relative to the ethylene monomer component contained in the olefin (the content of the alpha olefin monomer unit other than ethylene contained in the copolymer is most preferably less than 4% by mass), or the olefin is ethylene alone, then the peel strength can be further improved. It is generally known that adhesives or bonding treatments can cause the dielectric properties of laminates such as copper-clad laminates to deteriorate, and it is preferred that even if such treatments are not performed, a peel strength of more than 1N / mm can be given in accordance with the measurement of Japanese Industrial Standard (JIS) C6481:1996. In this way, for the uncured or semi-cured thermoplastic composition of the present invention, even if adhesive coating and bonding treatment are not particularly performed, curing treatments such as heating and pressurizing treatments can be used to bond with copper foil for wiring. However, in the present invention, regarding the bonding to copper foil and other components, there is no hindrance to the implementation of other countermeasures (adhesive coating, bonding treatment, etc.) for imparting bonding, including further adding the above-mentioned "surface modifier".
[0142] In another embodiment of the present invention, the following curable composition can also be provided, which comprises an olefin-aromatic vinyl compound-aromatic polyene copolymer that satisfies the following conditions (1) to (4), and a monomer that is greater than 0 mass parts and less than 10 mass parts relative to 100 mass parts of the copolymer, wherein the above-mentioned monomer is one or more selected from the group consisting of an aromatic vinyl compound monomer, an aromatic polyene monomer, and a polar monomer.
[0143] (1) The number average molecular weight of the copolymer is 5,000 to 100,000.
[0144] (2) The aromatic vinyl compound monomer in the copolymer is an aromatic vinyl compound having 8 to 20 carbon atoms, and the content of the aromatic vinyl compound monomer unit is 0% by mass to 70% by mass.
[0145] (3) The aromatic polyene is one or more selected from polyenes having a carbon number of 5 to 20 and having a plurality of vinyl and / or vinylidene groups in the molecule, and the content of vinyl and / or vinylidene groups derived from the aromatic polyene unit is 1.5 to less than 20 in terms of number average molecular weight.
[0146] (4) The olefin is one or more selected from olefins having 2 to 20 carbon atoms, and the total of the olefin monomer units, the aromatic vinyl compound monomer units and the aromatic polyene monomer units is 100% by mass.
[0147] More preferably, the above monomer may be a polar monomer.
[0148] In addition, the following electrical insulating material can be provided, which is a cured product obtained by curing the curable composition, and has a storage elastic modulus of 5×10 5 Pa or more, preferably 1×10 6 Pa or more, and the dielectric constant at 23° C. and 10 GHz is 2.5 or less and 2.0 or more, and the dielectric loss tangent is 0.003 or less and 0.0005 or more.
[0149] The curable composition can be similar to the curable composition comprising the above-mentioned olefin-aromatic vinyl compound-aromatic polyene copolymer and the resin (hereinafter, referred to as the composition with the resin), and includes one or more selected from the group consisting of the above-mentioned solvent, curing agent, filler, flame retardant, and surface modifier. The curable composition exerts thermoplasticity and can be formed into various shapes including sheets such as the composition with the above-mentioned resin. The curable composition can be used as a varnish together with a solvent, similar to the composition with the resin. The present invention is a cured body obtained by curing the curable composition, which can show various physical properties similar to the cured body of the composition with the resin. The curable composition can be made into a laminate comprising a layer containing the curable composition and copper foil, similar to the composition with the resin, or it can be made into a cured body formed by curing the laminate.
[0150] In addition, the composition involved in the above-mentioned embodiment of the present invention, or the composition involved in other embodiments can be cured together with the LCP (Liquid Crystal Polymer, liquid crystal polymer) layer under milder curing conditions to impart high bonding strength. The so-called LCP layer here can specifically be an LCP sheet or an LCP film. Therefore, for example, various laminates including an LCP sheet, a metal foil (preferably a copper foil), and the composition of the present invention can be made. The number of layers and the order of lamination of the laminate are arbitrary. As such an example of the present invention, the composition of the present invention is useful as an adhesive layer between a metal foil (copper foil) and an LCP sheet. The composition of the present invention can show high adhesion to both metal foil and LCP sheet. In the past, the bonding of LCP sheet and copper foil required heating to the melting point of LCP (approximately 280°C to 330°C, or a temperature close thereto) for compression bonding. However, by using the composition of the present invention as an adhesive layer, LCP and metal foil can be bonded by compression bonding at a lower temperature, substantially near the curing temperature of the composition of the present invention. At this time, the low dielectric constant and low dielectric loss tangent of the cured body of the composition of the present invention give the usefulness of wiring, especially for high-frequency signal transmission, to the laminate. As another example of the laminate, the following structure can be cited: from the side opposite to the LCP layer side, the metal wiring (preferably copper wiring) disposed on the LCP layer is covered by the cured body layer of the composition of the present invention. This is the purpose of the so-called covering layer on the LCP substrate wiring.
[0151] Here, LCP (liquid crystal polymer) refers to a thermoplastic polymer having a liquid crystal state or optically birefringent properties when melted. As LCP, there are lyotropic liquid crystal polymers that show liquid crystal properties in a solution state and thermotropic liquid crystal polymers that show liquid crystal properties when melted. Liquid crystal polymers are classified into type I, type II, and type III according to the thermal deformation temperature, and can be of any type. As liquid crystal polymers, for example, thermoplastic aromatic liquid crystal polyesters, or thermoplastic aromatic liquid crystal polyester amides into which amide bonds are introduced, etc. can be cited. LCP can also be a polymer formed by further introducing an imide bond, a carbonate bond, a carbodiimide bond, a bond from an isocyanate (isocyanurate bond, etc.) into an aromatic polyester or an aromatic polyester amide. As LCP, a molten liquid crystal forming polyester formed by 2-hydroxy-6-naphthoic acid and p-hydroxybenzoic acid can be used, for example, LCP resin (model A-5000, melting point 280°C) manufactured by Ueno Pharmaceutical Co., Ltd.
[0152] Regarding the melting point of LCP, according to the DSC method, it is preferably 220 to 400°C, and more preferably 260 to 380°C. When the melting point is within the above range, films and sheets with excellent extrusion moldability and excellent heat resistance can be obtained. Such LCP can be obtained, for example, from Ueno Pharmaceutical Co., Ltd., Sumitomo Chemical Co., Ltd., and POLYPLASTICS CO., LTD. Here, LCP sheet refers to a known LCP sheet, and its thickness is also arbitrary. LCP sheet can be obtained by known methods such as T-die extrusion, blow molding, and endless belt (double belt pressing) method.
[0153] Example
[0154] Hereinafter, the present invention will be described using examples, but the present invention is not construed as being limited to the following examples.
[0155] The copolymers obtained in the Synthesis Examples and Comparative Synthesis Examples were analyzed by the following method.
[0156] The content of vinyl units derived from ethylene, hexene, styrene, and divinylbenzene in the copolymer is determined by 1 H-NMR is determined based on the intensity of the peak area attributable to each. The sample is dissolved in deuterated 1,1,2,2-tetrachloroethane and the measurement is performed at 80 to 130°C.
[0157] The molecular weight was determined by using GPC (gel permeation chromatography) to determine the number average molecular weight (Mn) in terms of standard polystyrene. The measurement was performed under the following conditions.
[0158] (When the number average molecular weight is 1000 or more)
[0159] Chromatographic columns: Two TSK-GEL MultiporeHXL-M ×300 mm (manufactured by Tosoh Corporation) were connected in series and used.
[0160] Column temperature: 40°C
[0161] Solvent: THF
[0162] Liquid delivery flow: 1.0ml / min.
[0163] Detector: RI detector (differential refractive index detector) 0083]
[0165] When the copolymer is difficult to dissolve in THF solvent, for example, when the styrene content of the ethylene-styrene-divinylbenzene copolymer is less than 40% by mass, the molecular weight in terms of standard polystyrene is determined by the following high temperature GPC method. The measurement is performed under the following conditions.
[0166] Device: HLC-8121GPC / HT manufactured by Tosoh Corporation
[0167] Chromatographic column: TSKgelGMHHR-H(20)HT, ×300mm3 root,
[0168] Column temperature: 140°C
[0169] Detector: RI,
[0170] Solvent: o-dichlorobenzene,
[0171] Liquid delivery flow: 1.0ml / min,
[0172] Sample concentration: 0.1wt / vol%, injection volume: 100μL
[0173] <Tensile test>
[0174] According to JIS K-6251:2017, a film with a thickness of about 1 mm was cut into a 1 / 2 dumbbell test piece shape, and the tensile modulus, tensile breaking strength, and tensile breaking elongation were determined at 23°C and a tensile speed of 500 mm / min using Tensilon UCT-1T manufactured by Orientic.
[0175] <DSC measurement>
[0176] DSC measurement was performed using DSC6200 manufactured by Seiko Electronics Co., Ltd. under nitrogen flow. That is, 10 mg of resin was used, 10 mg of α-alumina was used as a reference, and an aluminum pan was used. After heating from room temperature to 240°C at a heating rate of 10°C / min in a nitrogen atmosphere, the temperature was cooled to -120°C at a rate of 20°C / min. Then, while heating to 240°C at a heating rate of 10°C / min, DSC measurement was performed to determine the glass transition temperature. The glass transition temperature referred to here is the extrapolated glass transition starting temperature of JIS K7121:2012, that is, the temperature of the intersection of the straight line extending from the low temperature side baseline to the high temperature side and the tangent line drawn at the point where the slope of the curve of the step-shaped change part of the glass transition becomes the maximum.
[0177] <Measurement of storage elastic modulus and crosslink density>
[0178] The dynamic viscoelasticity measuring device (RSA-III from Rheometric Company) was used to measure the storage elastic modulus at a frequency of 1 Hz and a temperature range of -60°C to +300°C. The sample for measurement (3 mm × 40 mm) was cut from a film having a thickness of about 0.1 mm to 0.3 mm. The main measurement parameters related to the measurement are as follows.
[0179] Measuring frequency 1Hz
[0180] Heating rate: 3℃ / min
[0181] Sample measurement length 13mm
[0182] Test Type = Dynamic Temperature Ramp (DTempRamp)
[0183] Initial Static Force: 5.0g
[0184] Auto Tension Sensitivity: 1.0g
[0185] Max Auto Tension Rate: 0.033mm / s
[0186] Maximum applied strain: 1.5%
[0187] Minimum allowable torque (Min Allowed Force) 1.0g
[0188] Strain 0.1%
[0189] <Water absorption>
[0190] The measurement was carried out according to ASTM D570-98.
[0191] <Dielectric constant and dielectric loss (dielectric loss tangent)>
[0192] The dielectric constant and dielectric loss tangent were measured at 10 GHz at 23° C. using a cavity perturbation method (8722ES network analyzer manufactured by Agilent Technology, cavity resonator manufactured by Kanto Denshi Applied Development) using a 1 mm×1.5 mm×80 mm sample cut from a sheet.
[0193] <Volume resistivity>
[0194] The measurement was performed at room temperature using a film having a thickness of about 0.5 mm in accordance with JIS K6911:2006.
[0195] <Olefin-aromatic vinyl compound-aromatic polyene copolymer>
[0196] With reference to the manufacturing method of Japanese Patent Publication No. 2009-161743, Japanese Patent Publication No. 2010-280771, and International Publication No. WO00 / 37517, the amount of monomers, ratio, polymerization pressure, and polymerization temperature are appropriately changed to obtain copolymers of P-1 to P-4. The total of olefin monomer units, aromatic vinyl compound monomer units, and aromatic polyene monomer units is set to 100 mass %. The composition, number average molecular weight, and glass transition temperature of the copolymer are shown in Table 1.
[0197] The raw materials are as follows.
[0198] Divinylbenzene used was divinylbenzene manufactured by Nippon Steel & Sumitomo Chemical Co., Ltd. (a mixture of meta and para positions, with a divinylbenzene purity of 81%). As for the difunctional polyphenylene ether oligomer (OPE-2St, number average molecular weight 1200), the toluene solution product manufactured by Mitsubishi Gas Chemical Co., Ltd. was further diluted with toluene, and a large amount of methanol was added to precipitate methanol, and then air-dried and dried under reduced pressure to obtain a powdered polyphenylene ether oligomer, and the powdered polyphenylene ether oligomer was used. As SEBS, Tuftec H-1041 manufactured by Asahi Kasei Chemicals Co., Ltd. (number average molecular weight 58000) was used. As 1,2-polybutadiene, liquid polybutadiene manufactured by Nippon Soda Co., Ltd. was used: product name B-3000 (number average molecular weight 3200). As the curing agent, dicumyl peroxide (trade name “Percumyl D”) or 2,5-dimethyl-2,5-bis(tert-butylperoxy)-3-hexyne (trade name “Perhexyne 25B”) manufactured by NOF Corporation was used.
[0199] [Table 1]
[0200]
[0201] [Table 2]
[0202]
[0203] Example 1
[0204] Using a Brabender Plasti-Corder (model PL2000 manufactured by Brabender), the pre-mixed resin P-1 (ethylene-styrene-divinylbenzene copolymer) and the monomer and resin composition shown in Table 2 (in the table, the composition represents mass parts) were added, and mixed at 120°C at a rotation speed of 30 times / min for 10 minutes, and further 1 mass part of a curing agent (dicumyl peroxide, manufactured by NOF Corporation) was added relative to 100 mass parts of the resin and monomer composition, and mixed for 5 minutes under the same conditions to prepare a composition. The obtained composition was clamped between a mold frame and two Teflon (registered trademark) sheets, and the mold frame and two Teflon (registered trademark) sheets were tightly and sealed, and the heat and pressure method (120°C, time 5 minutes, pressure 5 MPa) was used to pressurize to obtain sheets (uncured sheets) of various thicknesses (thickness 1.0 mm, 0.5 mm, etc.). The obtained sheet was sandwiched with a Teflon (registered trademark) sheet by a glass plate, a load was applied to make them close, and they were heated at 120° C. for 30 minutes, at 150° C. for 30 minutes, and then at 180° C. for 120 minutes to cure. After curing, the glass plate, Teflon (registered trademark) sheet and mold frame were removed to obtain a film-like cured body of the composition of the present invention.
[0205] Examples 2 to 6, Comparative Example 1
[0206] The same steps as in Example 1 were used to prepare a composition with the formulation of Table 2 (the formulation in the table indicates parts by mass). Press molding was performed in the same manner as in Example 1, and a curing treatment was performed. In Example 5, the raw materials other than the curing agent were kneaded at 100°C for 10 minutes at a rotation speed of 50 times / min, and then a curing agent (diisopropylbenzene peroxide) was added, and kneading was further performed under the same conditions for 5 minutes. In Example 4, Perhexyne 25B was used as a curing agent. It should be noted that in Example 3, Example 4, and Example 7 described later, 1,2-polybutadiene was added before adding the curing agent. The properties (room temperature) of the compositions before curing of Examples 1 to 6 and Comparative Example 1 were all soft resin-like and semi-hard resin-like sheets, which were easy to handle as sheets. Even if they were peeled off from the Teflon (registered trademark) sheet after pressurization, the self-adhesiveness of the sheet itself was low, and it could be handled as a separate sheet. The embodiments that meet the preferred conditions of the present invention are easy to be molded as thermoplastic resins in an uncured state.
[0207] Examples 7 to 8, Comparative Examples 2 to 4
[0208] In a container equipped with a heating and cooling jacket and a stirring blade, raw materials other than the curing agent are charged in the formulation of Table 2, heated and stirred at 60°C to obtain a varnish-like (viscous liquid) composition. Then, a curing agent is added and stirred to dissolve. Diisopropylbenzene peroxide is used as the curing agent. The obtained varnish-like composition is injected into a Teflon (registered trademark) mold frame on a Teflon (registered trademark) sheet, and the solvent is fully volatilized by using an air supply dryer at about 100°C and then further under reduced pressure. Then, the Teflon (registered trademark) mold frame is carefully removed, and a soft resin-like sheet is obtained. The obtained sheet is further clamped between a mold frame and two Teflon (registered trademark) sheets, and is tightly and sealed. It is pressurized by a heating and pressing method (120°C, time 5 minutes, pressure 1.5MPa) to obtain sheets (uncured sheets) of various thicknesses (thickness 1.0mm, 0.5mm, etc.). The sheet is easy to handle, and even if it is peeled off from the Teflon (registered trademark) sheet, the sheet itself has low self-adhesion and can be handled as a separate sheet. That is, it is easy to perform molding processing as a thermoplastic resin in an uncured state. Use a glass plate to clamp the obtained sheet together with the Teflon (registered trademark) sheet, apply a load to make it close, heat it at 120°C for 30 minutes, heat it at 150°C for 30 minutes, and then heat it at 200°C for 120 minutes to cure it. After curing, remove the glass plate, Teflon (registered trademark) sheet and mold frame to obtain a cured sheet of the composition of the present invention.
[0209] The cured sheets obtained in Examples 1 to 8 did not undergo melting fracture at 300°C in the viscoelastic spectrum measurement, and the elastic modulus could be measured. The storage elastic modulus at 300°C (573K) was 5×10 5 In addition, the crosslinking density calculated from the storage elastic modulus at 300°C (573K) is higher than 3×10 -5 mol / cm 3 , indicating that crosslinking is fully carried out. In addition, all of them show a tensile elastic modulus of less than 3GPa and more than 3MPa. In addition, the tensile strength at break is more than 5MPa and less than 50MPa, and the tensile elongation at break is more than 50% and less than 250%. The dielectric constant and dielectric loss tangent also meet the scope of the present invention. The water absorption of the cured sheets obtained in Examples 1 to 8 is less than 0.1% by mass, and the volume resistivity is 1×10 15Ω·cm or more. The dielectric constant of the cured sheets obtained in Examples 1 to 8 measured at 10 GHz was below 2.5 and above 2.0, and the dielectric loss tangent was below 0.003 and above 0.0005, showing good low dielectric properties. As for the cured body of the sheet obtained in Comparative Example 1, the storage elastic modulus and crosslinking density at 300°C also did not meet the conditions of the present invention. As for the sheet obtained in Comparative Example 2, a large number of cracks were generated, which was not suitable for use as an insulating material, and various physical property measurements were not performed. As for the sheets obtained in Comparative Examples 3 and 4, the preferred ranges of the dielectric constant and dielectric loss tangent of the present invention were not met, so no other evaluations were performed.
[0210] <Peel strength from the rough surface of copper foil>
[0211] Copper foil used was made by Mitsui Mining & Smelting Co., Ltd. (VSP series, TQ-M7-VSP, thickness 12μm). The rough surface of the copper foil was placed in contact on an uncured sheet with a thickness of 0.3mm (which was obtained by press-molding the composition of Example 1 at 120°C and 5MPa for 2 minutes), and a mold frame with a thickness of 0.3mm was used. A heating and pressing machine was used to heat and press at 120°C for 30 minutes, then at 150°C for 30 minutes, and then at 200°C for 120 minutes under a pressure of 5MPa, thereby bonding and curing the sheet to the copper foil. The peel strength with the copper foil was measured in accordance with Japanese Industrial Standard (JIS) C6481:1996 and evaluated by 90° peeling. As a result, the peel strength was 2.3N / mm. The peel strength of the composition of Example 4 with the copper foil was also measured in the same way, and the result was 1.5N / mm.
[0212] <Synthesis of ethylene-styrene-divinylbenzene copolymer oligomer>
[0213] With reference to the manufacturing method described in Japanese Patent Laid-Open No. 9-40709, an autoclave with a capacity of 10 L and a stirrer and a heating and cooling jacket is used. As a catalyst, dimethylmethylenebiscyclopentadienyl zirconium dichloride is used. As a cocatalyst, methylaluminoxane (made by Tosoh Reika Co., Ltd., MMAO-3A toluene solution) is used. As a solvent, cyclohexane is used. As raw materials, styrene, divinylbenzene, and ethylene are used. The monomer amount, ratio, polymerization pressure, and polymerization temperature are appropriately changed to carry out polymerization. 1-isopropanol is added to the obtained polymerization solution, and then, in the presence of an inhibitor, a large amount of methanol is added to recover the copolymerized oligomer. The copolymerized oligomer O-1 is vacuum dried at 50° C. for 2 days and nights.
[0214] <Olefin-aromatic vinyl compound-aromatic polyene copolymer>
[0215] With reference to the manufacturing method of Japanese Patent Publication No. 2009-161743 and Japanese Patent Publication No. 2010-280771, the amount of monomer, ratio, polymerization pressure and polymerization temperature are appropriately changed to obtain the copolymer of P-5. The total of olefin monomer unit, the above-mentioned aromatic vinyl compound monomer unit and the aromatic polyene monomer unit is taken as 100 mass %. The composition, number average molecular weight and glass transition temperature of the obtained O-1 and P-5 are shown in Table 3.
[0216] As bismaleimide, BMI-1500 manufactured by Designer Molecules Inc. was used.
[0217] Silica used was fused silica manufactured by Denka without pretreatment, SFP-130MC (d50 = 0.6 μm, specific surface area 6.2 m 2 / g, true specific gravity is 2.26g / cm 3 ).
[0218] [Table 3]
[0219]
[0220] Embodiment 9, 10
[0221] Into a container equipped with a heating and cooling jacket and a stirring blade, the raw materials other than the curing agent are charged in the formulation of Table 4, heated and stirred at 60°C to obtain a varnish-like (viscous liquid) composition. Then, the curing agent is added and stirred to dissolve. Perhexyne 25B is used as the curing agent. The obtained varnish-like composition is injected into a Teflon (registered trademark) mold frame on a Teflon (registered trademark) sheet, and the solvent is fully volatilized by using an air supply dryer at about 60°C and then further under reduced pressure. The obtained sheet is clamped together with the Teflon (registered trademark) sheet using a mirror metal plate, a load is applied to make it fit tightly, and it is heated at 120°C for 30 minutes, at 150°C for 30 minutes, and then at 200°C for 120 minutes to cure it. After curing, the metal plate, Teflon (registered trademark) sheet and mold frame are removed to obtain a cured sheet of the composition of the present invention.
[0222] Embodiment 11
[0223] To the varnish-like composition obtained by the same operation as in Examples 9 and 10, a silica filler (50% by volume of the silica filler relative to 50% by volume of the resin component) was added, and the mixture was further stirred. The obtained slurry-like varnish was further stirred with Awatori Rentaro (manufactured by Thinky Co.), and poured into a Teflon (registered trademark) mold frame on a Teflon (registered trademark) sheet. The solvent was fully volatilized by using an air-supplemented dryer at about 60°C and then further under reduced pressure. The obtained sheet was clamped together with the Teflon (registered trademark) sheet with a mirror-finished metal plate, a load was applied to make it close, and the mixture was heated at 120°C for 30 minutes, at 150°C for 30 minutes, and then at 200°C for 120 minutes to cure. After curing, the metal plate, Teflon (registered trademark) sheet and mold frame were removed to obtain a cured sheet of the composition of the present invention.
[0224] [Table 4]
[0225]
[0226] The formulations in the table are expressed in parts by mass.
[0227] ※Add 1 part by mass to 100 parts by mass of the total raw materials other than the curing agent.
[0228] The cured bodies obtained in Examples 9 and 10 and the cured body with filler added obtained in Example 11 all meet the requirements of the cured body of the present invention.
[0229] Embodiment 12, 13
[0230] <Evaluation as an Adhesive for Copper Foil and LCP (Liquid Crystal Polymer) Sheet>
[0231] Using the varnish obtained in Examples 9 and 10, the adhesion between the copper foil and the LCP sheet was evaluated in the following manner. As the copper foil, the above-mentioned copper foil was used, as the LCP sheet, LCP resin (model A-5000, melting point 280°C) manufactured by Ueno Pharmaceutical Co., Ltd. was used, and a sheet with a thickness of 100 μm obtained by the method described in International Publication No. WO2020 / 153391 was used. The varnish was applied to the LCP sheet, and the solvent was first removed by air drying at 60°C, and then the solvent was carefully removed in a non-foaming manner at 60°C under normal pressure to vacuum. The thickness of the varnish layer after the solvent was removed was about 30 μm. The rough surface of the copper foil was made to fit the varnish side of the sheet from which the solvent was removed, and a press was used to pressurize 5 MPa under vacuum, and then heated at 120°C for 30 minutes, heated at 150°C for 30 minutes, and then heated at 180°C for 120 minutes to cure it. The sheet was cut into pieces with a width of 10 mm and a length of 100 mm, and the peel strength between the LCP sheet and the copper foil was measured and evaluated by peeling at 90° according to Japanese Industrial Standard (JIS) C6481:1996. In the case of using the varnish obtained in Example 9, the peel strength was 1.4 N / mm. In the case of using the varnish obtained in Example 10, it was 1.3 N / mm. The peeling surface was observed, and as a result, peeling occurred at the interface between the solidified body from the varnish and the LCP sheet. Therefore, it was concluded that the peel strengths of the LCP sheet and the solidified body from the varnish were 1.4 N / mm and 1.3 N / mm, respectively. In addition, in the same test piece, it was concluded that the peel strengths of the copper foil and the solidified body from the varnish were each higher than the above values.
[0232] Comparative Example 5
[0233] Only the copper foil and the LCP sheet were heat-pressed and bonded using a press machine under the same conditions as in the example, but the two were not substantially bonded.
[0234] <Example according to the second aspect>
[0235] Based on the following raw materials, copolymers P-1a to P-4a according to the second embodiment were prepared with the compositions shown in Table 5 according to the above-mentioned production method.
[0236] Divinylbenzene used was divinylbenzene (meta- and para-mixed product, divinylbenzene purity 81%) manufactured by Nippon Steel & Sumitomo Chemical Co., Ltd. BVPE (1,2-bis(vinylphenyl)ethane) was synthesized using the synthesis method described in Japanese Patent Gazette No. 2003-212941. It is a mixture of meta-meta, meta-para, and para-para. 1,2-PBd used was B-3000 manufactured by Nippon Soda Co., Ltd. For the difunctional polyphenylene ether oligomer (OPE-2St, number average molecular weight 1200), the toluene solution product manufactured by Mitsubishi Gas Chemical Co., Ltd. was further diluted with toluene, and a large amount of methanol was added to precipitate methanol, air-dried, and then dried under reduced pressure to obtain a powdered polyphenylene ether oligomer, and the powdered polyphenylene ether oligomer was used. SEBS used was H-1041 manufactured by Asahi Kasei Chemicals Co., Ltd. Diisopropyl peroxide (Percumyl D) manufactured by NOF Corporation was used as a curing agent.
[0237] [Table 5]
[0238]
[0239] Table 6 shows the formulations of the examples and comparative examples.
[0240] [Table 6]
[0241]
[0242]
[0243] Example 1a
[0244] Using Brabender Plasti-Corder (Model PL2000 manufactured by Brabender), the pre-mixed copolymer P-1a (ethylene-styrene-divinylbenzene copolymer) and the monomer were added, and mixed at 100°C and 50 times / min for 5 minutes. Further, 1 part by mass of a curing agent (dicumyl peroxide, manufactured by NOF Corporation) was added relative to 100 parts by mass of the total of the copolymer and the monomer, and mixed at 100°C, 50 times / min for 5 minutes to prepare a composition. The obtained composition was clamped between a mold frame and two Teflon (registered trademark) sheets, and the mold frame and two Teflon (registered trademark) sheets were tightly and sealed, and the sheets (uncured sheets) of various thicknesses (thickness 1.0 mm, 0.5 mm, etc.) were obtained by heat and pressure method (120°C, time 5 minutes, pressure 5 MPa). The obtained sheet was clamped together with a Teflon (registered trademark) sheet by a glass plate, a load was applied to make them close, and they were heated at 120° C. for 30 minutes, at 150° C. for 30 minutes, and then at 180° C. for 120 minutes to cure. After curing, the glass plate, Teflon (registered trademark) sheet and mold frame were removed to obtain a film-like cured body of the composition of the present invention.
[0245] Examples 2a to 4a, Comparative Examples 1a to 2a
[0246] The same steps as in Example 1a were used to prepare a composition with the formulation shown in Table 6 (the formulation in the table indicates parts by mass). The composition was press-formed and cured in the same manner as in Example 1a. The properties (room temperature) of the compositions before curing of Examples 1a to 4a were all soft resin-like or semi-hard resin-like sheets, which were easy to handle as sheets. Even if the sheet was peeled off from the Teflon (registered trademark) sheet after pressurization, the sheet itself had low self-adhesion and could be handled as a separate sheet. The embodiments that meet the preferred conditions of the present invention are easily molded as thermoplastic resins in an uncured state.
[0247] On the other hand, for Comparative Examples 1a and 2a, a glass container equipped with a stirrer and a hot water jacket was used, and the raw materials were mixed by stirring at about 60°C in advance, a curing agent was added, and the mixing was carried out under the same condition for 10 minutes. Press molding was carried out in the same manner as in Example 1a, and a curing treatment was performed. The properties (room temperature) of the compositions before curing obtained in Comparative Examples 1a and 2a were both semi-solid viscous resins. When they were peeled off from the release sheet (Teflon (registered trademark) sheet), they showed stickiness and high self-adhesion, making it difficult to handle them as a single sheet, and they could only be handled in a state clamped by the release sheet.
[0248] The cured product of the composition sheet obtained in Examples 1a to 4a did not undergo melting fracture at 300°C in the viscoelastic spectrum measurement, and the elastic modulus could be measured. The storage elastic modulus at 300°C (573K) was 5×10 5 In addition, the crosslinking density calculated from the storage elastic modulus at 300°C (573K) is higher than 3×10 -5 mol / cm 3 , indicating that crosslinking is fully carried out. In addition, the tensile elastic modulus is less than 3GPa and greater than 3MPa. In addition, the tensile strength at break is greater than 5MPa and less than 50MPa, and the tensile elongation at break is greater than 50% and less than 250%. The dielectric constant and dielectric loss tangent also meet the scope of the present invention. The water absorption of the cured films obtained in Examples 1a to 4a is less than 0.1% by mass, and the volume resistivity is 1×10 15 On the other hand, the cured products of the sheets obtained in Comparative Examples 1a and 2a had too low tensile modulus at room temperature, and the storage modulus and crosslinking density at 300° C. did not satisfy the conditions of the present invention.
[0249] <Peel strength from the rough surface of copper foil>
[0250] Copper foil used was made by Mitsui Mining & Smelting Co., Ltd. (VSP series, TQ-M7-VSP, thickness 12 μm). The rough surface of the copper foil was placed in contact on an uncured sheet with a thickness of 0.3 mm (which was obtained by press-molding the composition of Example 1a at 120°C and 5 MPa for 2 minutes), and a mold frame with a thickness of 0.3 mm was used. A heating and pressing machine was used to heat and press at 120°C for 30 minutes under a pressure of 5 MPa, then at 150°C for 30 minutes, and then at 180°C for 120 minutes, thereby bonding and curing the sheet to the copper foil. The peel strength with the copper foil was measured and evaluated by 90° peeling according to Japanese Industrial Standard (JIS) C6481:1996. As a result, the peel strength was 1.7 N / mm.
[0251] According to the above results, the cured product obtained by curing the composition of the present invention is a cured product with excellent low dielectric properties and electrical insulation, elastic modulus, heat resistance, water resistance in a specific range, and strength (elastic modulus) under normal temperature and high temperature domains is sufficient in practice. In addition, the peel strength with copper foil is also sufficient in practice. In addition, it is also possible to show a high peel strength with LCP (liquid crystal polymer) sheet under milder conditions. The curable composition shows the following thermoplasticity: it can present a state of a film-shaped solid, and can be melted by heating below the curing conditions to be formed into various shapes and solidified. Therefore, it can be easily formed into various shapes including sheets, and then heat cured. The cured product can be suitably used as an electrical insulating material for high frequency. The cured product can be suitably used as an electrical insulating material for film, an electrical insulating material for high frequency. With regard to the present invention, in particular, the content of the monomer (monomer) component in the composition is small, and it can also be substantially not included. The composition of the present invention can be used as a cover layer film, a solder resist film, a build-up film, a bonding sheet, a cover layer sheet, a bump sheet for a flip chip bonding machine, an interlayer insulating agent, and an interlayer adhesive in an uncured state. The present invention can be used as a printed substrate, a flexible printed substrate, a CCL (copper clad laminate) substrate, and a FCCL (flexible copper clad laminate) substrate. In addition, it can be used as an insulating layer for a substrate.
Claims
1. A curable composition comprising an olefin-aromatic vinyl compound-aromatic polyene copolymer satisfying the following conditions (1) to (4), and an added resin, wherein the added resin is one or more selected from the group consisting of hydrocarbon elastomers, polyphenylene ethers, olefin-aromatic vinyl compound-aromatic polyene copolymer oligomers, and aromatic polyene resins, wherein the storage elastic modulus of a cured product of the curable composition at 300° C. is 5×10 5 Pa or above, (1) The number average molecular weight of the copolymer is 5000 or more and 100,000 or less; (2) the aromatic vinyl compound monomer is an aromatic vinyl compound having 8 to 20 carbon atoms, and the content of the aromatic vinyl compound monomer unit is higher than 0% by mass and is less than 70% by mass; (3) the aromatic polyene is one or more selected from polyenes having a plurality of vinyl and / or vinylidene groups in the molecule and having a carbon number of 5 to 20, and the content of vinyl and / or vinylidene groups derived from the aromatic polyene unit is 1.5 to less than 20 in terms of number average molecular weight; (4) The olefin is one or more selected from olefins having 2 to 20 carbon atoms, and the total of the olefin monomer units, the aromatic vinyl compound monomer units and the aromatic polyene monomer units is 100% by mass.
2. The curable composition according to claim 1, wherein The additive resin is contained in an amount of 1 to 500 parts by mass based on 100 parts by mass of the copolymer.
3. The curable composition according to claim 1 or 2, wherein The added resin is one or more selected from the group consisting of polyphenylene ether and 1,2-polybutadiene. 4 . The curable composition according to claim 1 , further comprising at least one monomer selected from the group consisting of an aromatic vinyl compound monomer, an aromatic polyene monomer, and a polar monomer.
5. The curable composition according to claim 4, wherein The monomer is contained in an amount of 10 parts by mass or less based on 100 parts by mass of the copolymer. 6 . A varnish-like curable composition comprising the curable composition according to claim 1 and a solvent. 7 . The curable composition according to claim 1 , further comprising a curing agent. 8 . The curable composition according to claim 1 , further comprising one or more selected from the group consisting of a filler, a flame retardant, and a surface modifier. 9 . A molded article formed from the curable composition according to claim 1 .
10. The molded article according to claim 9, which is a sheet.
11. A cured product obtained by curing the curable composition according to any one of claims 1 to 8.
12. The solidified body according to claim 11, wherein the storage elastic modulus at 300°C is 1×10 6 Pa or above.
13. The cured product according to claim 11 or 12, which is an electrical insulating material.
14. An electrical insulating material, which is a cured product obtained from the following composition, wherein the composition comprises an olefin-aromatic vinyl compound-aromatic polyene copolymer satisfying the following conditions (1) to (4), and one or more additional resins selected from the group consisting of hydrocarbon elastomers, polyphenylene ethers, olefin-aromatic vinyl compound-aromatic polyene copolymer oligomers, and aromatic polyene resins, wherein the electrical insulating material has a storage elastic modulus at 300°C of 5×10 5 Pa or more, and the dielectric constant at 23°C and 10 GHz is 2.5 or less and 2.0 or more, and the dielectric loss tangent is 0.003 or less and 0.0005 or more, (1) The number average molecular weight of the copolymer is 5000 or more and 100,000 or less; (2) the aromatic vinyl compound monomer is an aromatic vinyl compound having 8 to 20 carbon atoms, and the content of the aromatic vinyl compound monomer unit is higher than 0% by mass and is less than 70% by mass; (3) the aromatic polyene is one or more selected from polyenes having a plurality of vinyl and / or vinylidene groups in the molecule and having a carbon number of 5 to 20, and the content of vinyl and / or vinylidene groups derived from the aromatic polyene unit is 1.5 to less than 20 in terms of number average molecular weight; (4) The olefin is one or more selected from olefins having 2 to 20 carbon atoms, and the total of the olefin monomer units, the aromatic vinyl compound monomer units and the aromatic polyene monomer units is 100% by mass.
15. A curable composition comprising an olefin-aromatic vinyl compound-aromatic polyene copolymer satisfying the following conditions (1) to (4), and a monomer in an amount of more than 0 parts by mass and less than 10 parts by mass relative to 100 parts by mass of the copolymer, wherein the monomer is one or more selected from the group consisting of an aromatic vinyl compound monomer, an aromatic polyene monomer, and a polar monomer, wherein the storage elastic modulus of a cured product of the curable composition at 300° C. is 5×10 5 Pa or above, (1) The number average molecular weight of the copolymer is 5000 or more and 100,000 or less; (2) the aromatic vinyl compound monomer in the copolymer is an aromatic vinyl compound having 8 to 20 carbon atoms, and the content of the aromatic vinyl compound monomer unit is higher than 0% by mass and is 70% by mass or less; (3) the aromatic polyene is one or more selected from polyenes having a plurality of vinyl and / or vinylidene groups in the molecule and having a carbon number of 5 to 20, and the content of vinyl and / or vinylidene groups derived from the aromatic polyene unit is 1.5 to less than 20 in terms of number average molecular weight; (4) The olefin is one or more selected from olefins having 2 to 20 carbon atoms, and the total of the olefin monomer units, the aromatic vinyl compound monomer units and the aromatic polyene monomer units is 100% by mass.
16. The curable composition according to claim 15, wherein The monomer is a polar monomer.
17. An electrical insulating material, which is a cured product obtained by curing the curable composition according to claim 15 or 16, wherein the storage elastic modulus of the electrical insulating material at 300°C is 5×10 5 Pa or more, and the dielectric constant at 23° C. and 10 GHz is 2.5 or less and 2.0 or more, and the dielectric loss tangent is 0.003 or less and 0.0005 or more. 18 . A laminate comprising a copper foil and a layer containing the curable composition according to claim 1 .
19. A laminate comprising an LCP layer and a layer containing the curable composition according to any one of claims 1 to 8, 15, and 16. 20 . A laminate comprising a copper foil, an LCP layer, and a layer containing the curable composition according to claim 1 .
21. A cured product obtained by curing the laminated product according to any one of claims 18 to 20.
Citation Information
Patent Citations
Preparation of polyethylene having low dielectric loss
JP1977031272B2
Silicon nitride block
JP1990120213A
Production of melamine-phenolic resin molding material
JP1990140215A
Thermosetting resin composition having low dielectric constant
JP1994192392A
Production of ethylene / Aromatic vinyl compound copolymer
JP1997040709A